2019
DOI: 10.1042/bsr20181771
|View full text |Cite
|
Sign up to set email alerts
|

Role of mast cells in the generation of a T-helper type 2 dominated anti-helminthic immune response

Abstract: Mast cells are long-lived, innate immune cells of the myeloid lineage which are found in peripheral tissues located throughout the body, and positioned at the interface between the host and the environment. Mast cells are found in high concentrations during helminth infection. Using Kitw-sh mast cell deficient mice, a recently published study in Bioscience Reports by Gonzalez et al. (Biosci. Rep., 2018) focused on the role of mast cells in the immune response to infection by the helminth Hymenolepis diminuta. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…Interleukin (IL)-4, IL-5, IL-9 and IL-13 are important cytokines that play key roles in type 2 immunity, and are usually involved in allergic diseases or during helminthic parasitic infections (8,9). Th2 cells and certain myeloid cells are considered the primary source of these type 2 cytokines (10,11); however, recent studies have reported that a rare subpopulation of innate lymphocytes are the predominant source (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL)-4, IL-5, IL-9 and IL-13 are important cytokines that play key roles in type 2 immunity, and are usually involved in allergic diseases or during helminthic parasitic infections (8,9). Th2 cells and certain myeloid cells are considered the primary source of these type 2 cytokines (10,11); however, recent studies have reported that a rare subpopulation of innate lymphocytes are the predominant source (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…IL-13 together with IL-4, IL-5 and IL-10 belong to the group of cytokines of the type 2 response profile, since they promote the induction of the humoral immune response by favoring the production of antibodies by B cells, diminish the cellular immune response and lead to an anti-inflammatory environment (74,75). The type response profile 2 cytokines and other mediators produced by MC are able to direct, amplify and perpetuate the Th2 immune response in allergy, helminthic infection and in oral immunization models (76)(77)(78)(79)(80). Interestingly type 2 response has been recently associated as a relevant mechanism during bacterial infection, in particular during the skin infection with S. aureus, by favoring IgE production and effector mechanisms regulated by MC (81).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, mast cells continue accumulating in the mucosa and actively secrete proteases for more than 28 days after the expulsion of T. muris from the intestine ( 40 , 41 ). Mast cell-dependent expulsion has also been reported for the rat tapeworm H. diminuta using Kit W-sh -deficient mice that displayed delayed worm expulsion ( 42 ). Similarly, mast cells have been shown to be essential for adult expulsion using a novel model of mast cell deficiency (in Cpa3-Cre mice) that does not affect basophil number, contrary to c-kit -deficient mice ( 43 ).…”
Section: Evidence For Myeloid Cell Killing and Control Of Infectionmentioning
confidence: 91%